Comparative Legal Analysis of the Use of Electronic Format of Criminal Cases and the Procedure under the Code of Criminal Procedure of the Russian Federation - Ivanov, Dmitriy; Grinenko, Aleksandr; Fadeev, Pavel; Ermakov, Sergey; Antimonova, Svetlana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The article deals with the foreign experience of digitalisation in the preliminary investigation. Conservative views of law enforcers and legislators on this issue dominate the Russian Federation. There are only small steps towards digitalising preliminary investigations in our country. At the same time, it has been established that the introduction of various information systems and automated workstations into practice, which was supposed to create a unified system and network of broad coverage, has not happened due to the lack of a unified request from the system of investigative bodies and technical capabilities, as well as lack of an urgent need for changes in the working procedure on the part of investigators and interrogators. In conclusion, the authors conclude that there are currently only minor steps towards digitalisation of pre-trial investigations and creating an electronic format for criminal cases in the Russian Federation. However, the rapidly developing information and telecommunication technologies will also do their job in this aspect, which will lead to the creation and successful testing of the topic studied by the authors.